Kolaborasi Intrusion Detection System Berbasis Publish/Subscribe - Samsul Arifin; Endang Setyati (Jurnal Ilmiah Teknologi Informasi Asia, 2012)
Dependency of information technology man would be increasing along with run of time. Of course with anything information technology becomes quicker, practical, and relative hardly easy, distance which so far bermil-mil will felt so near. Together with that also hence new problem also will emerge that is about network security. One of factor becoming threat in network security is existence of infiltrator or attacker. Attacker will infiltrate into network suddenly without the knowledge from admin network. All kinds of intention of possible attacker just fad, looks around data or takes it is even will become very dangerous if unwillingly destroying data and system. Beginning of from problem to hence at this handing out will study about how making system network security by using snort IDS ( Intrution Detection System)and IPtables firewall bases on publish/subscribe. Snort and IPtables each would be each other cooperate to detect existence of infiltrator and tries to prevent it admission in network. Because there is many host in network hence applied by mechanism of publish/subscribe with a purpose to at the time of one of host detects existence of attack hence would soon is sent to topic server to be propagated for all host in network, so that every host can prevent infiltrator to do exploitation Keywords: snort IDS, iptables firewall, publish/subscribe, elvin router